Preserving cultural-roots: Indigenous parenting practices in shaping ethical foundations in children - Habibat Bolanle Abdulkareem; Jamila Yusuf; Kamoru Abidoye Tiamiyu (Himpunan Pengembang Kurikulum Indonesia, 2025)
In an increasingly globalised world, the preservation of cultural heritage is vital in nurturing the ethical and moral development of children. Indigenous parenting practices, deeply embedded in ancestral traditions and communal values, provide a distinct framework for shaping ethical behaviour and instilling virtues such as respect, responsibility, empathy, and community consciousness. This study aims to explore the role of indigenous parenting practices in fostering ethical development in children and to assess their impact on children’s ethical decision-making and the intergenerational transmission of cultural norms. Employing a qualitative research approach, the study conducted a comprehensive review of relevant literature and analyzed case studies from various indigenous communities. Key indigenous parenting methods identified include storytelling, communal living, rites of passage, and traditional mentoring systems all of which serve as tools for ethical education. The findings reveal that these practices effectively nurture ethical values by embedding children within a strong cultural identity, fostering a sense of communal responsibility, and reinforcing virtues such as honesty, respect, and empathy. The study underscores the importance of integrating these time-tested values into modern child-rearing practices to reinforce ethical foundations in children while preserving cultural heritage. Abstrak Dalam dunia yang semakin mengglobal, pelestarian warisan budaya sangat penting dalam memelihara perkembangan etika dan moral anak-anak. Praktik pengasuhan adat, yang tertanam dalam tradisi leluhur dan nilai-nilai komunal, menyediakan kerangka kerja yang berbeda untuk membentuk perilaku etis dan menanamkan nilai-nilai seperti rasa hormat, tanggung jawab, empati, dan kesadaran komunitas. Studi ini bertujuan untuk mengeksplorasi peran praktik pengasuhan adat dalam membina perkembangan etika pada anak-anak dan untuk menilai dampaknya terhadap pengambilan keputusan etis anak-anak dan transmisi norma-norma budaya antargenerasi. Dengan menggunakan pendekatan penelitian kualitatif, studi ini melakukan tinjauan komprehensif terhadap literatur yang relevan dan menganalisis studi kasus dari berbagai komunitas adat. Metode pengasuhan adat utama yang diidentifikasi meliputi mendongeng, kehidupan komunal, ritus peralihan, dan sistem bimbingan tradisional yang semuanya berfungsi sebagai alat untuk pendidikan etika. Temuan tersebut mengungkapkan bahwa praktik-praktik ini secara efektif memelihara nilai-nilai etika dengan menanamkan anak-anak dalam identitas budaya yang kuat, menumbuhkan rasa tanggung jawab komunal, dan memperkuat nilai-nilai seperti kejujuran, rasa hormat, dan empati. Studi ini menggarisbawahi pentingnya mengintegrasikan nilai-nilai yang telah teruji waktu ini ke dalam praktik pengasuhan anak modern untuk memperkuat landasan etika pada anak-anak sambil melestarikan warisan budaya. Kata kunci: adat, akar budaya, anak-anak, praktik pengasuhan